ASSESSMENT OF THE BRICS MONETARY POLICY - A. A. Aliev (Вестник университета, 2020)
A set of theoretical, practical and methodological issues of determining the economic status of the state, based on the use of indicators of stability, dynamic and qualitative indicators of state development has been examined for obtaining a generalized assessment of monetary policy on the example of the BRICS countries. The fuzzy set tools, peer review, graphic analysis, and tools for calculating common integral indicators, based on selected indicators, reflecting its state, have been used. The methodology will be interesting to state authorities, investment funds and investors. The results of the study can be used in investment decisions and economic analysis of countries. The practical significance of the obtained results сonsists in a generalized assessment and an opportunity to evaluate the economic development of the country, taking into account the monetary policy of the BRICS countries.